Non-lysosomal Activation in Macrophages of Atlantic Salmon (Salmo salar) After Infection With Piscirickettsia salmonis - Pérez-Stuardo, Diego; Morales-Reyes, Jonathan; Tapia, Sebastián; Ahumada, Diego E.; Espinoza, Allison; Soto-Herrera, Valentina; Brianson, Bernardo; Ibaceta, Valentina; Sandino, Ana M.; Spencer, Eugenio; Vallejos-Vidal, Eva; Reyes-López, Felipe E.; et al. (Frontiers in Immunology, 2019)
Piscirickettsia salmonis is a facultative intracellular pathogen and etiological agent of the systemic disease salmonid rickettsial septicemia. It has been suggested that P. salmonis is able to survive in host macrophages, localized within a vacuole like-compartment which prevents lysosomal degradation. However, the relevant aspects of the pathogenesis of P. salmonis as the host modulation that allow its intracellular survival have been poorly characterized. In this study, we evaluated the role of lysosomes in the response to P. salmonis infection in macrophage-enriched cell cultures established from Atlantic salmon head kidneys. Bacterial infection was confirmed using confocal microscopy. A gentamicin protection assay was performed to recover intracellular bacteria and the 16S rDNA copy number was quantified through quantitative polymerase chain reaction in order to determine the replication of P. salmonis within macrophages. Lysosomal activity in Atlantic salmon macrophage-enriched cell cultures infected with P. salmonis was evaluated by analyzing the lysosomal pH and proteolytic ability through confocal microscopy. The results showed that P. salmonis can survive ≥120 h in Atlantic salmon macrophage-enriched cell cultures, accompanied by an increase in the detection of the 16S rDNA copy number/cell. The latter finding suggests that P. salmonis also replicates in Atlantic salmon macrophage-enriched cell cultures. Moreover, this bacterial survival and replication appears to be favored by a perturbation of the lysosomal degradation system. We observed a modulation in the total number of lysosomes and lysosomal acidification following infection with P. salmonis. Collectively, the results of this study showed that infection of Atlantic salmon macrophages with P. salmonis induced limited lysosomal response which may be associated with host immune evasion mechanisms of P. salmonis that have not been previously reported.